Gambaran Pasien Penyakit Jantung Dan Pembuluh Darah Di RSUD Lamaddukkellleng Sengkang Tahun 2023 - Ali Seppo, Muh. Pasca Rivaldi (PT.Mantaya Idea Batara, 2025)
Cardiovascular disease (CVD) remains one of the significant health challenges in the world. This type of research uses a quantitative descriptive research design. This study used a total sampling of 200 patients with heart and blood vessel disease. Data were analyzed using Microsoft Excel by dividing the data into 5 parts of heart disease: coronary heart disease, heart failure, arrhythmia, stable angina pectoris, and other heart diseases. The age of majority of patients aged 41-60 years, amounting to 89 patients (44.5%), and those aged> 60 years (44.5%). The most common heart disease treated at RSUD lamaddukkelleng Sengkang in 2023 is coronary heart disease, with a total of 95 patients (47.5%), followed by heart failure cases and cases of stable angina pectoris with a total of 44 patients (22%). The most common comorbidity in heart disease patients treated at RSUD Lamaddukkelleng Sengkang in 2023 is hypertension, with a total of 74 patients (51.7%). The length of hospitalization of heart disease patients treated at Lamaddukkelleng Sengkang Hospital in 2023 was primarily for 3 days, namely 72 patients (36%), followed by 4 days, namely 53 patients (26.5%), and the most extended treatment was 13 days as many as 1 patients (0.5%). The number of heart disease patients who died at Lamaddukkelleng Hospital in 2023 was 29 people, or 14.5% died during treatment at Lamaddukkelleng Hospital in 2023. The average age of heart patients treated was 89% aged 41 - 60. While based on gender, male heart patients are more than female heart patients. The most common heart disease is Coronary Heart Disease (CHD). The length of hospitalization of heart patients varied from 1 day to the longest of 13 days. About 36% of cardiac patients were treated for 3 days, and 26.5% were treated for 4 days. Cardiac patients who died during treatment at Lamaddukkelleng Hospital in 2023 there were a total of 29 patients (14.5%).